The genus Tyrinthia Bates, 1866 in Ecuador (Coleoptera, Cerambycidae, Lamiinae, Hemilophini) - Galileo, Maria Helena M.; Mcclarin, Jim; Santos-Silva, Antonio (Zootaxa, 2017)
Tyrinthia frontalis (Guérin-Méneville, 1855) is redescribed, formally recorded from Ecuador, and its type locality is questioned. Tyrinthia napoensis sp. nov. is described from Ecuador. Tyrinthia paraba Martins & Galileo, 1991, and T. turuna Martins & Galileo, 1993 are new country records for Ecuador. A key to species of Tyrinthia from Ecuador is provided.